2014
DOI: 10.1186/1477-5751-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in hSOD1 copy number significantly impacts ALS phenotype presentation in G37R (line 29) mice: implications for the assessment of putative therapeutic agents

Abstract: BackgroundIn vivo animal models of familial amyotrophic lateral sclerosis (fALS) are widely used to delineate the potential role that genetic mutations play in the neurodegenerative process. While these models are extensively used for establishing the safety and efficacy of putative therapeutics during pre-clinical development, effective clinical translation of pharmacological interventions has been largely unsuccessful.ResultsIn this report we compare a recent cohort of G37R (line 29) mice generated from mati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Importantly, however, these differences depend on the presence of genetic modifiers (Heiman-Patterson et al, 2005). Furthermore, female mice from another SOD1 G37R line (line 29) have reduced survival and tend to have a delayed onset (Zwiegers et al, 2014), which is reminiscent of our present finding in loxSOD1 G37R mice. These results contrast with a recent study on Chinese familial ALS patients carrying SOD1 mutations which identified that women tended to have a slower progression and longer survival after onset (Tang et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Importantly, however, these differences depend on the presence of genetic modifiers (Heiman-Patterson et al, 2005). Furthermore, female mice from another SOD1 G37R line (line 29) have reduced survival and tend to have a delayed onset (Zwiegers et al, 2014), which is reminiscent of our present finding in loxSOD1 G37R mice. These results contrast with a recent study on Chinese familial ALS patients carrying SOD1 mutations which identified that women tended to have a slower progression and longer survival after onset (Tang et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Sex-specific differences have been identified in other SOD1 mouse models and in patients carrying SOD1 mutations, but they did not consistently point toward a faster or more severe disease in one sex (Hayworth and Gonzalez-Lima, 2009;Kim et al, 2012;Zwiegers et al, 2014;Pfohl et al, 2015;Tang et al, 2019). For instance, male SOD1 G93A mice have an earlier onset than female SOD1 G93A mice (Hayworth and Gonzalez-Lima, 2009;Kim et al, 2012;Pfohl et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Our recent experience with the G37R model underscores this dilemma in that we had generated a colony of animals from commercial breeders with an uncharacterized drop in copy number. As expected, these presented with a concomitant increase in lifespan and delay in disease progression (83). Transgene level variation can arise due to meiotic recombination.…”
Section: Impediments To Replicability Between Preclinical Studiesmentioning
confidence: 99%
“…On the other hand, it promoted axonal regeneration process after nerve injury and protected rat motor neurons in culture against glutamate-induced excitotoxicity and iPSC-derived motor neurons from apoptosis. of disease presentation (Zwiegers et al, 2014;Lutz, 2018); secondly, the overexpression of human wild-type SOD1 causes axonopathy in mice, challenging the role of the mutation as the driver of pathology (Joyce et al, 2011).…”
Section: Pacap and Alsmentioning
confidence: 99%
“…Although SOD1 G93A mice is the widely used animal model, reproducing motor defects similar to that observed in ALS-affected patients, there are important caveats to acknowledge. Firstly, the mSOD1 mouse model has a propensity to spontaneously delete copy number which can alter the severity of disease presentation ( Zwiegers et al, 2014 ; Lutz, 2018 ); secondly, the overexpression of human wild-type SOD1 causes axonopathy in mice, challenging the role of the mutation as the driver of pathology ( Joyce et al, 2011 ).…”
Section: Pacap and Alsmentioning
confidence: 99%